Implementation of The Profile Strengthening of Pancasila Student Profile (P5) in Building Student Character in First Middle School - Ni Wayan Wini Widarini; Ni Ketut Suterji (Jayapangus Press, 2023)
Technological progress is one of the factors that influence the achievement of educational goals. The negative side can give rise to ethical and moral crises that hit society. The government launched the Pancasila Student Profile as one of the efforts to improve the quality of education in Indonesia which emphasizes character building. Strengthening the Pancasila Student Profile focuses on cultivating character, as well as instilling abilities in daily life in individual students through school culture, namely intra-curricular and extra-curricular learning, projects to strengthen Pancasila student profiles. The purpose of this article is to conceptually describe how the strengthening of the Pancasila student profile project is implemented in junior high schools with the independent teaching curriculum implemented at SMP Negeri 1 Susut in the 2022/2023 academic year. The hope of this article is that practitioners in the field of education can understand more deeply about the implementation of the project to strengthen the profile of Pancasila students in junior high schools. This study uses a type of qualitative research, with a descriptive approach. Data collection techniques used are observation, interviews and literature research. Based on the results of observations made by researchers at SMP Negeri 1 Susut, the Pancasila Student Profile Strengthening Project is a focus especially on grade 7 students with a strategy; differentiated learning, learning by project (P5) and habituation. The Pancasila Student Profile Strengthening Project was carried out by taking the theme of entrepreneurship and a sustainable lifestyle.